In the age of the smart machine : - Zuboff, Shoshana (Basic Books, 1988)
Contents: Dilemmas of transformation in the age of the smart machine; Knowledge and computer-mediated Work; The abstraction of industrial work; The abstraction of industrial work; The dominion of the smart machine...